68 Why are patients not more involved in their own safety? A questionnaire-based survey in a multi-ethnic north london population. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Assassi, Zouina; Ahmedani, Iman; Yoong, Wai; Abdinasir, Rhama; Adofo Kwakye, Michael; Taylor, Harriet; Chandrakumar, Danya; Nauta, Maud; Denning, Max
Abstract : Background: An estimated 8 50 000 cases of unintentional medical injuries occur every year, at least half of which are thought to be preventable. Patients receiving palliative care are particularly vulnerable to medical errors and their consequences. Patient participation in their own safety has well-demonstrated benefits in reducing errors. Understanding how patients feel about participating in their own safety and how to improve patient engagement could help reduce medical errors in palliative care. The authors sought to examine patient participation in a range of safety-related behaviours and investigate how they varied with different patient demographics. Methods: A 20-point questionnaire was employed exploring safety-related behaviours, particularly looking at patient willingness to challenge healthcare professionals and to notify them of potential errors. Data on sex, age, ethnicity, English language proficiency, duration in the United Kingdom, employment and education status was also collected. Results: 195 patients were invited to participate in this study and 175 patients completed the questionnaire. Female patients who had tertiary education, those who were fluent in English and under the age of 60 years were statistically more likely to feel responsible for their own safety and take an active role in their safety. Older male patients of lower education status are statistically less likely to question staff on hand hygiene. Conclusion: Despite numerous campaigns to improve patient involvement many still do not participate in their own safety. Patients without tertiary education, patients over 60, and those who are not fluent in English are much less willing to challenge healthcare professionals about safety-related issues. Understanding the impact of patient demographics on participation in safety behaviours could help to create novel, more targeted strategies to improve patient safety. This could effectively reduce preventable medical errors in palliative care medicine where patients are more vulnerable to such errors.